2017
DOI: 10.1371/journal.pone.0169539
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of TST and IGRA in Diagnosis of Latent Tuberculosis Infection in a High TB-Burden Setting

Abstract: BackgroundThere are currently two tests for diagnosing latent tuberculosis infection (LTBI); TST and IGRA. However, it is still unclear that which one of these tests performs better in high TB-burden settings.Methods1511 household contacts of pulmonary TB patients were enrolled to compare the performance of TST and IGRA for LTBI. At baseline all participant underwent testing for IGRA [QuantiFERON-TB® Gold In-tube (QFT-GIT) assay] and TST [2 tuberculin unit (TU), purified protein derivative (PPD), RT23, Staten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 22 publications
6
74
0
3
Order By: Relevance
“…However, these assays failed to discriminate between different phases of infection nor to predict the occurrence of disease . Indeed, it was recently shown that neither TST nor IGRAs predicted subsequent development of active TB among household contacts of pulmonary TB patients during follow‐up …”
Section: Discussionmentioning
confidence: 99%
“…However, these assays failed to discriminate between different phases of infection nor to predict the occurrence of disease . Indeed, it was recently shown that neither TST nor IGRAs predicted subsequent development of active TB among household contacts of pulmonary TB patients during follow‐up …”
Section: Discussionmentioning
confidence: 99%
“…Further, due to their comparable performances in different settings, replacing the TST by IGRAs as a public health intervention is not recommended [3]. The fact that neither test has the desired sensitivity to detect LTBI is also evident from a recent study from north India in which, during the followup period, incidence of TB in test-positive (TST or IGRA) and test-negative contacts was comparable [4]. Another recent report has suggested that certain differences in adaptive immunity in a subset of persons who are exposed to Mtb could be responsible for their test-negativity for TST and IGRA [5].…”
Section: Introductionmentioning
confidence: 99%
“…Variability in immune responses can contribute to the difficulty of TB diagnosis. Currently, the tuberculin skin test and blood IFNγ release assay are used to assess TB infection (Sharma et al, 2017). Due to the different mechanisms by which these tests operate, results do not always agree (Gallant et al, 2010).…”
Section: Immune Diversity and The Challenge Of Global Tb Diagnostics mentioning
confidence: 99%